Changes in beef carcass composition with changes in animal weight and finish - Tuma, H.J.; Kropf, Donald H.; Kolstad, S.P.; Mackintosh, D.L. (Kansas Agricultural Experiment Station, 2011)
Information on animal growth and development, although complex and not fully understood, is necessary to determine the stage at which a beef animal will produce the most desirable carcass. True growth involves an increase in the structural tissues (muscle, bone and organs) and should be distinguished from increases by fat deposition. Optimum time to slaughter animals is when muscle growth and quality are at their most desirable combination.
Keywords: Beef; Growth; Carcass; Tissues